The TKI Era in Chronic Leukemias - Danilo De Novellis; Fabiana Cacace; Valeria Caprioli; William G. Wierda; Kris M. Mahadeo; Francesco Paolo Tambaro (MDPI AG, 2021)
Tyrosine kinases are proteins involved in physiological cell functions including proliferation, differentiation, and survival. However, the dysregulation of tyrosine kinase pathways occurs in malignancy, including hematological leukemias such as chronic myeloid leukemia (CML) and chronic lymphocytic leukemia (CLL). Particularly, the fusion oncoprotein BCR-ABL1 in CML and the B-cell receptor (BCR) signaling pathway in CLL are critical for leukemogenesis. Therapeutic management of these two hematological conditions was fundamentally changed in recent years, making the role of conventional chemotherapy nearly obsolete. The first, second, and third generation inhibitors (imatinib, dasatinib, nilotinib, bosutinib, and ponatinib) of BCR-ABL1 and the allosteric inhibitor asciminib showed deep genetic and molecular remission rates in CML, leading to the evaluation of treatment discontinuation in prospective trials. The irreversible BTK inhibitors (ibrutinib, acalabrutinib, zanubrutinib, tirabrutinib, and spebrutinib) covalently bind to the C481 amino acid of BTK. The reversible BTK inhibitor pirtobrutinib has a different binding site, overcoming resistance associated with mutations at C481. The PI3K inhibitors (idelalisib and duvelisib) are also effective in CLL but are currently less used because of their toxicity profiles. These tyrosine kinase inhibitors are well-tolerated, do have some associated in-class side effects that are manageable, and have remarkably improved outcomes for patients with hematologic malignancies.